The Influence of Motivation and Work Environment on the Work Productivity of West Sulawesi Province Tourism Office Employees - Sari, Kiki Wirdayani (Golden Ratio of Data in Summary, 2025)
Employees are the main asset of an organization and have a strategic role within the organization, namely as thinkers, planners and controllers of organizational activities. This research aims to analyze the influence of motivation and work environment on the work productivity of the West Sulawesi Province Tourism Office. This type of research is observational with a cross sectional study design. The population of this study was 70 customers and a sample of 70 using the census method which made the population the sample in the research. The collected data was analyzed using multiple linear regression tests. The research results showed that the majority of respondents were male 38 (54.3%), education 43 (61.4%) and occupation 41 (58.6%). The results of multiple linear regression analysis that have an influence are, namely, Motivation (p=0.012) which has a significant effect on the work productivity of the Tourism Service, and Work Environment (p=0.000) which has a significant effect on the work productivity of the Tourism Office. The conclusion is that the work environment variable has the most influence on work productivity with a value of 5,369. The suggestion is that the Tourism Department continues to properly motivate its employees and continue to pay attention to the work environment of its employees.